Sustainable leadership and wellbeing of healthcare personnel: A sequential mediation model of procedural knowledge and compassion - Abid, Ghulam; Contreras, Francoise; Rank, Susanne; Ilyas, Sehrish (Frontiers in Psychology, 2023)
Introduction: In healthcare organizations, saving patients’ lives while maintaining the staff's wellbeing, performance and competencies were challenging during the COVID-19 pandemic. Although the complexity of healthcare settings is widely recognized, the pandemic evidenced the necessity of attending to the employees' wellbeing in such a sector. This research aims to examine the effect of sustainable leadership on wellbeing of healthcare personnel. Furthermore, we also evaluate whether procedural knowledge and compassion act as mediators in such a relationship. Methods: The hypothesized model was tested in healthcare organizations in a South Asian country, and the data were collected during the pandemic crisis. A total of 366 health personnel (physicians and nurses) participated in this research. With Hayes' PROCESS macro, we examined all the direct and indirect paths, including sequential mediation. Results: The findings confirm the impact of sustainable leadership on wellbeing and this relationship is also mediated by procedural knowledge and compassion. Discussion/Conclusion: Sustainable leadership fosters wellbeing among healthcare workers via the sequential mediation of procedural knowledge and compassion. Study findings suggest that sustainable leaders can trigger procedural knowledge among employees which in turn crafts the state of compassion in them that leads to their wellbeing. Theoretical and practical implications are discussed in light of study findings.